Development of high-quality new reference genomes for Asian rice - CGIAR Research Program on Rice (2020)
New high quality reference genomes will allow more complete discovery of genomic variation in Asian rice. The genomes were produced by PacBio sequencing and assembles validated by optical mapping. This will enable deeper analyses of the Rice Array antenna panel.